Linking Technology Readiness and Service Utilization: A TRI Study of SMEs in Java, Indonesia - Resanti Lestari; Fitri Lestari; Fatmasari Endayani; Dyah Setiawati; Syahyuti Syahyuti (Jurnal Manajemen dan Kewirausahaan, 2025)
Micro, Small, and Medium Enterprises (SMEs) in Java Island represent a strategic sector contributing significantly to Indonesia’s economy. However, many SMEs face challenges in adopting integrated technologies, limiting their ability to compete and grow in the digital era. One key issue is the lack of understanding of their technological readiness and the absence of a standardized model to evaluate technology adoption comprehensively. This study addresses this gap by developing a model to measure the Technology Readiness Index (TRI) of SMEs, serving as a foundation for strategies aimed at improving digital adoption. The model builds upon the Technology Readiness Index (TRI) by Parasuraman, focusing on psychological dimensions such as optimism, innovativeness, discomfort, and insecurity. The study adopts a quantitative approach through a year-long survey involving SMEs from various sectors across Java. Data was collected using TRI-based questionnaires and analyzed using regression techniques to explore the relationship between readiness and actual technology use. The findings indicate a significant and positive relationship between SMEs’ technology readiness and their use of technology-based services. In other words, SMEs that demonstrate higher levels of readiness tend to adopt technology more actively. Although technology readiness is not the sole factor, it plays an important role in influencing adoption behavior. These results highlight the importance of tailored interventions that align with SMEs' readiness index to support their digital transformation journey. The study recommends using the TRI model as a diagnostic tool to design effective support policies for SMEs in developing countries.